Mapping degradation signals and pathways in a eukaryotic N-terminome [data set] - Kats, Ilia; Khmelinskii, Anton; Kschonsak, Marc; Huber, Florian; Knieß, Robert A.; Bartosik, Anna; Knop, Michael (Universität, 2018)
Data accompanying the paper "Mapping degradation signals and pathways in a eukaryotic N-terminome"